Embattled [videorecording (DVD)] - Dorff, Stephen, 1973-; Dorff, Stephen, 1973-; Faison, Donald, 1974-; Reaser, Elizabeth, 1975-; Taghmaoui, Saïd (Shout! Factory, IFC Films, 2020)
Although a successful fighter in the world of MMA, Cash chooses flight when he finds out his second son is born with a developmental disorder, leaving his first son as caretaker while he continues to make his fortune in the ring. Now grown, Jett decides to follow in his father's fighting footsteps and confront him head-on in the ring, where Cash must face his past in a battle neither father nor son can win.